G-Jitter induced mixed convection flow and heat transfer of micropolar nanofluids flow over an inclined stretching sheet - Rawi, N. A. (American Institute of Physics Inc., 2016)
g-Jitter induced mixed convection flow of micropolar nanofluids past an inclined stretching sheet is numerically studied in this paper. Copper (Cu) in water based is considered. The governing partial differential equation is transformed into non-dimensional form by using appropriate non-dimensional variables and then solved by using Keller-box method. The behaviour of physical quantities such as skin friction and heat transfer coefficients as well as the velocity, microrotation and temperature profiles are investigated for both strong and weak concentration of microelements. The numerical results show that, the values of reduced skin friction and heat transfer coefficient are increased by increasing the material parameter but produce an opposite behaviour with the increasing in nanoparticles volume fraction parameter.